Self-assessment of pubertal stage in overweight children - Bonat, Sandra; Pathomvanich, Annatura; Keil, Margaret F; Field, Alison E; Yanovski, Jack A (Pediatrics (Evanston), 2002)
For those with normal body habitus, self-assessments have been reported to yield Tanner stage ratings similar to those found by actual examinations. Little is known about whether such self-assessments are accurate in obese children. We therefore determined the reliability of Tanner stage self-assessments in both nonobese and obese children. We studied 244 children age 6 to 12 years, 135 girls and 109 boys, 41% of whom were obese (body mass index > or =95th percentile for age and gender). Girls rated both breast and pubic hair development and boys rated pubic hair development using a standardized series of drawings accompanied by explanatory text. After self-ratings were completed, a pediatric endocrinologist or trained nurse practitioner who was blinded to subjects' self-ratings examined each subject. Self-ratings of breast Tanner stage were concordant with actual stage in 48%, overestimated in 25%, and underestimated in 27% of nonobese girls. By contrast, breast Tanner stage was overestimated by 38% of obese girls and was underestimated by only 12%. On average, obese girls overestimated actual Tanner breast stage by 0.47 +/- 0.9 stages. Pubic hair ratings were largely concordant with actual pubic hair stage in both obese and nonobese girls. Both nonobese and obese boys significantly overestimated actual Tanner pubic hair stage, by 0.51 +/- 1.1 stages and 0.31 +/- 0.8 stages, respectively. We conclude that, in children 6 to 12 years of age, self-assessment cannot be used to determine reliably the breast Tanner stage of obese girls or the pubic hair stage of boys.